2005
DOI: 10.3758/bf03195294
|View full text |Cite
|
Sign up to set email alerts
|

A memory-based account of automatic numerosity processing

Abstract: We investigated the mechanisms responsible for the automatic processing of the numerosities represented by digits in the size congruity effect (Henik & Tzelgov, 1982). The algorithmic model assumes that relational comparisons of digit magnitudes (e.g., larger than {8,2}) create this effect. If so, congruity effects ought to require two digits. Memory-based models assume that associations between individual digits and the attributes "small" and "large" create this effect. If so, congruity effects ought only to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
(30 reference statements)
2
16
0
Order By: Relevance
“…The results of a recent study probing the SCE (Choplin & Logan, 2005) reinforce the idea that numerals are associated instinctively with the left or right side of space. These authors found that people selected the physically larger member of the pair 4 2 faster than they did that of the pair 4 2 (the SCE).…”
Section: Is There An Association Between the Numerals 1-4 (Qua Shapessupporting
confidence: 72%
See 2 more Smart Citations
“…The results of a recent study probing the SCE (Choplin & Logan, 2005) reinforce the idea that numerals are associated instinctively with the left or right side of space. These authors found that people selected the physically larger member of the pair 4 2 faster than they did that of the pair 4 2 (the SCE).…”
Section: Is There An Association Between the Numerals 1-4 (Qua Shapessupporting
confidence: 72%
“…The numerals 1-4 are small in virtually all natural and experimental contexts, regardless of the overall range. Choplin and Logan (2005) suggested that "the smallest digits are most strongly associated with the attribute 'small' and most weakly associated with the attribute 'large'"(p. 27). Choplin and Logan's data suggest that people retrieve instances of number-space and number-magnitude associations from past experience, commensurate with a learning account of stimulus-response mapping.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We should insist here that we need not, and do not, assume that these two operations are arithmetical in the sense of relying on the same psychological mechanisms as in more standard arithmetical paradigms. Clearly, the limited number of stimuli and the repetition of many trials with them encourages a simple memory retrieval strategy (see the work of G. Logan and colleagues on automatization as memory retrieval, notably in the case of arithmetic: Choplin & Logan (2005); Klapp, Boches, Trabert, & Logan (1991);Logan (2002);Logan (1992Logan ( , 1988; ; Reder & Ritter (1992)). However, none of our predictions depend on this first operation being ''truly" arithmetical in any sense of the term.…”
Section: Terminology and General Methodsmentioning
confidence: 99%
“…We assumed that associations between the digits and the category High were strong for the higher digits and became weaker for lower digits. For simplicity, we assumed that association strength varied linearly Schneider and Logan (2005) with the value of the digits, with association strengths decreasing from 1-9 for the category Low and increasing from 1-9 for the category High (Choplin & Logan, 2005;Miller & Gelman, 1983;Shepard, Kilpatric, & Cunningham, 1975). We assumed a common slope, m, for both linear functions (formally, -m and m).…”
Section: Target Representations and Target Functionsmentioning
confidence: 99%